2013
DOI: 10.1002/jgra.50583
|View full text |Cite
|
Sign up to set email alerts
|

Stationary planetary wave and nonmigrating tidal signatures in ionospheric wave 3 and wave 4 variations in 2007–2011 FORMOSAT‐3/COSMIC observations

Abstract: [1] The wave 3 and wave 4 modulations of the Equatorial Ionization Anomalies are a robust feature of the low-latitude ionosphere, when viewed at constant local time. Although initially associated, respectively, with DE2 and DE3, nonmigrating diurnal tides in the mesosphere and lower thermosphere region, recent results have suggested that the wave 3 and wave 4 may also have significant contributions from other tidal and stationary planetary wave (SPW) signatures. We present observations of total electron conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 62 publications
(87 citation statements)
references
References 33 publications
(60 reference statements)
6
78
0
Order By: Relevance
“…In our in situ N e observations no saturation effect has been found for the absolute DE3 amplitudes. When looking at the relative amplitudes of these tides at low latitudes, S. found little dependence on solar activity, while Chang et al (2013) Fig. 4a) in our eyes is more reasonably explained by the modulation of the propagation conditions from the troposphere and stratosphere by QBO.…”
Section: Solar Activity Dependence Of the Nonmigrating Tidessupporting
confidence: 46%
See 1 more Smart Citation
“…In our in situ N e observations no saturation effect has been found for the absolute DE3 amplitudes. When looking at the relative amplitudes of these tides at low latitudes, S. found little dependence on solar activity, while Chang et al (2013) Fig. 4a) in our eyes is more reasonably explained by the modulation of the propagation conditions from the troposphere and stratosphere by QBO.…”
Section: Solar Activity Dependence Of the Nonmigrating Tidessupporting
confidence: 46%
“…That is why the absolute amplitudes of Chang et al (2013). By analyzing the TEC observations from the FORMOSAT-3/COSMIC during 2007-2011 they reported that the absolute amplitudes of all the tides contributing to WN4 (DE3, SE2 and SPW4) are directly related to the level of solar activity.…”
Section: Solar Activity Dependence Of the Nonmigrating Tidesmentioning
confidence: 99%
“…Hagan et al (2009) reported the existence of stationary planetary wave-4 (SPW4) oscillation in the upper mesosphere and lower thermosphere (MLT) region, caused by the nonlinear interaction between DE3 and the migrating tide DW1. Since then, the importance of stationary planetary waves, SPW4/SPW3, contributing to the longitudinal WN4/WN3 patterns in the upper atmosphere, has also been supported by both model simulations (e.g., Oberheide et al, 2011a;Pancheva et al, 2012) and in situ observations (e.g., Kil et al, 2010;Lühr and Manoj, 2013;Xiong and Lühr, 2013;Chang et al, 2013).…”
Section: Introductionmentioning
confidence: 79%
“…Analysis of migrating tidal signatures in F3/C TECs , as well as associated numerical experiments, yielded insight on the relations between ionospheric migrating tidal signatures and the corresponding features of zonal mean ionospheric local time variation isolated through such analysis. Such analysis is further extended to understanding the inter-annual variation of ionospheric tidal and stationary planetary waves (SPWs) signatures comprising the well-known "wave-4" modulation of the equatorial ionization anomalies (EIAs), a feature ultimately driven by modulation of the E-region dynamo by vertically propagating non-migrating (Chang et al 2013b). The results demonstrated that such atmosphere-ionosphere coupling was present during periods of both high and low solar activities, forming a persistent feature of ionospheric variability.…”
Section: Formosat-3/cosmicmentioning
confidence: 99%